The Standing Stone of Velmaio (Varese, North-Western Lombardy, Italy). From an Erratic Boulder to a Megalith? - Cristian Scapozza; Christian Ambrosi; Claudio Castelletti; Florian Cousseau; Susan Ivy-Ochs; Daniel Bernoulli (Open Quaternary, 2024)
A standing stone was found near Velmaio (Italy), on the valley floor of the Torrente Bévera. The analysis of its morphology and of traces on its surface on all faces showed that the block is not in an original position but was placed later in its vertical position. The standing stone is made of a dolomite breccia. The texture and, in particular, the lithological composition of the breccia corresponds to that of the Invorio Breccia known only from one locality some 30 km southwest of Velmaio. Surface exposure dating of the boulder surface with cosmogenic 36Cl gave an age of 89.72 ± 5.1 ka. The smooth surface of the standing stone and the absence of traces of quarrying and human transport suggest that the Velmaio boulder was exhumed from Pleistocene deposits. Original deposition of the boulder may have been during the Penultimate glaciation, occurring at around 140 ka. Based on typological correlation with recently discovered megalithism in Claro (Cantone Ticino, Switzerland), we may assume that the boulder was probably chosen because of its particular lithology, transported from the location of its original deposition as an erratic boulder to Velmaio and finally erected, as we suggest as a hypothesis, during the 3rd millennium BCE.